The Influence of English Proficiency, IT Knowledge and Working Experience of UUM Accounting Students Towards Accounting Anxiety - Elhaj, Mohamed Abulgasem (2009)
This study examines the relationship between English proficiency, IT knowledge,working experience and accounting anxiety. Data were collected from 85 postgraduate accountancy students registered at Universiti Utara Malaysia, College of Business.Results of this study supported the hypotheses regarding the relationships between English proficiency and accounting anxiety, IT knowledge and accounting anxiety, and general work experience and accounting anxiety. English proficiency appeared to have the greatest impact on the accounting anxiety, followed by IT knowledge and general work experience. The findings suggested that, possessing high English proficiency, IT knowledge and prior general work experience are important to reduce accounting anxiety among postgraduate accounting students. Surprisingly, work experience in accounting did not significantly influence accounting anxiety. This study has implications for practice. Findings of this study are important as accounting anxiety is well known to have negative impact on students’ academic achievement. Therefore,future students must ensure that they possess sufficient English proficiency, IT knowledge and skills, and work experience prior to joining postgraduate accounting programs.